Antibacterial Activity of a Novel Biocomposite Chitosan/Graphite Based on Zinc-Grafted Mesoporous Silica Nanoparticles - Jamshidi D (Dove Medical Press, 2020)
Donya Jamshidi, Mohammad Reza Sazegar Department of Chemistry, Islamic Azad University, Tehran, IranCorrespondence: Mohammad Reza SazegarDepartment of Chemistry, Islamic Azad University, North Tehran Branch, Hakimiyeh, Tehran, IranTel +98-9381199151Email m_r_sazegar@yahoo.comIntroduction: A novel biocomposite chitosan/graphite based on zinc-grafted mesoporous silica nanoparticles (CGZM-bio) was synthesized and the antibacterial activities of this compound along with that of Zn-MSN nanoparticles were investigated.Methods: The CGZM-bio biocomposite was synthesized using sol–gel and post-synthesis method under UV radiation. The characterizations of the samples were carried out using FTIR, XRD, SEM, and nitrogen adsorption and desorption. The antibacterial activity was carried out against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) after 18 h at 310 K.Results: The suspension samples of the Zn-MSN and CGZM-bio (2– 100 μg.mL− 1) presented antibacterial activities against S. aureus and E. coli. The minimum inhibitory concentration (MIC) values against E. coli for the Zn-MSN and CGZM-bio samples were 10 and 5 μg.mL− 1, respectively, while the MIC against S. aureus for both nanomaterials was 10 μg.mL− 1.Discussion: The antibacterial activities of these materials are due to the generation of radical oxygen species such as •OH, H2O2, and O2 2- during the UV radiation via the generation of the electron–hole pairs which in turn damage the bacteria cells. These nanomaterials may be used in biomedical devices as antibacterial agents.Keywords: Zn-MSN, Staphylococcus aureus, Escherichia coli, antimicrobial activity, UV radiation, electron–hole pair